Att stanna eller lämna: en kvalitativ studie baserad på självbiografier om kvarhållande och frigörande faktorer i kvinnors uppbrottsprocess från våldsamma relationer. - Raka,Edlira; Szász,Bettina (2025)
Intimate partner violence is a serious societal issue with far-reaching consequences for women's health, safety, and overall life conditions. This study explores how women who have experienced violence in heterosexual relationships describe their journey toward leaving their abusive partners. By analyzing five autobiographical narratives written by Swedish women, the study seeks to uncover emotional, psychological, and social processes that shape the path toward separation. The aim is to illuminate the complex interplay between inner emotional states—such as ambivalence, fear, hope, and love—and external factors like control, isolation, and social support. Using a thematic analysis, the narratives are examined through the theoretical lenses of traumatic bonding, normalization processes, and coping theory. These frameworks enable a deeper understanding of the paradoxical dynamics that bind women to their perpetrators, as well as the strategies they develop to endure and ultimately break free from violent relationships. The findings reveal that the decision to leave is seldom a single act but rather a prolonged and fragmented process, marked by recurring setbacks and moments of clarity. Key turning points often emerge when emotional and practical thresholds are crossed, such as threats to children, escalating violence, or external interventions. The autobiographies also illustrate how certain factors — like fear and children — can act both as obstacles and as catalysts for change. By centering women's voices and experiences, the study contributes valuable insights for professionals in social work and related fields. The study emphasizes the importance of understanding violence not only as a physical act but as a deeply embedded relational and emotional experience.
Keywords: intimate partner violence; autobiographical narratives; traumatic bonding; normalization; the leaving process